Pengendalian Internal dalam Sistem Akuntansi Pembelian PT Garuda Maxima Kanaka untuk Meningkatkan Efisiensi Pengelolaan Persediaan - Yuli Rulamarzuqoh; Sigit Puji Winarko; Andy Kurniawan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to evaluate the implementation of internal controls in the purchasing accounting system to improve the efficiency of merchandise inventory management at PT Garuda Maxima Kanaka. The company faces major problems related to recurring shortages and overstocks, which cause discrepancies between accounting records and the physical condition of goods. This condition creates inaccurate inventory data and delays in procurement of goods, which impact the smooth operation of the company. The method used in this study is a qualitative approach with a case study at PT Garuda Maxima Kanaka. Data collection techniques include interviews with relevant parties, observation of processes taking place in the finance and warehouse departments, and analysis of relevant documentation. Respondents in this study consisted of directors, finance staff, and warehouse managers who are directly involved in the purchasing accounting system and inventory management. The results of the study indicate that the purchasing accounting system implemented in the company has not been implemented consistently, particularly in terms of documentation and coordination between departments. Internal controls have been implemented, but are not optimal due to overlapping functions between the finance and warehouse departments, as well as a lack of regular evaluation of the implementation of existing procedures. These inefficiencies lead to inconsistencies in inventory data and delays in procurement of goods, which hamper the smooth operation of the company. This study recommends improvements to the purchasing accounting system, including a clear separation of functions between finance and warehouse, and the implementation of regular internal control evaluations to improve the efficiency of merchandise inventory management. These improvements are expected to minimize inventory-related issues and improve overall operational performance.